Guía para la implementación de un sistema integrado de gestión en la unidad administrativa especial de servicios públicos-uaesp, basado en las normas ntc-iso 9001:2008 y ntc-ohsas 18001: 2007 (2014)
The present work is oriented to the elaboration of a guide for the implementation of the Integrated Management System-SIG in the Special Administrative Unit of Public Services-UAESP, focused on a mission process and based on the norms NTC-ISO 9001: 2008 and NTC -OHSAS 18001: 2007. The Unit is an entity of the district order that guarantees the provision, coordination, supervision and control of the services of collection, transportation, final disposal, recycling and use of solid waste, cleaning of roads and public areas; the funeral services in the infrastructure of the District and of the public lighting service, and that orientates its efforts towards the satisfaction of the users and the society of Bogotá, D.C. Therefore, it has carried out a work in the implementation of the quality management system and is currently certified in the standards NTC-ISO 9001: 2008 and NTC-GP1000: 2009. In the same way, the UAESP has worked in the maintenance of the System of Quality Management - SGC and the Internal Control Standard Model - MECI, and wants to continue with the implementation of the other systems established in the district regulations and thus comply with the goal of the District Development Plan Bogotá Humana 2012-2016, "Implement in 100% of the entities of the district, the Integrated Management System. "For the preparation of the Guide, it began with the gathering of information, interviews and observation, to then make a diagnosis of the current situation of the entity and define in what way conditions is the system. Additionally, a review and analysis of the critical procedures and elements found in the diagnosis was made, finding that some QMS documents, such as the quality manual, were outdated and the Safety and Health Management System is not implemented. Occupational. Likewise, an analysis of the Collection, Sweeping and Cleaning Process was carried out, which showed that although the service providers of the cleaning service in the city are supervised on occupational safety issues, within the entity there is no contemplate this system. This is how the Occupational Health and Safety Management System was incorporated into the procedures associated with this process. In drawing up the Guide, it is concluded that the GIS starts internally in the entity and that the service providers are strategic allies for the implementation of it, however, if the entity does not have an implemented system, there is no complete work and there may be failures in the operation. To prevent this from happening, it is important to raise the awareness of senior management, staff, and interested parties and work together with them to obtain the results that have been proposed.